International monetary fund in the context of cooperation with Ukraine - Dmytrov, O. (ТДАТУ, 2018)
The process of globalization of the world economy creates new factors for the development and transformations of the world‘s economic and financial systems. The existing level of interaction between countries requires coordination of the actions of individual governments in developing a unified international strategy for social and economic development
Keywords: financial market; Ukraine; political transformations; globalization; economic benefit